Interrogating harmful cultural practices: gender, culture and coercion - Longman, Chia; Bradley, Tamsin (Routledge, Taylor & Francis Group, 2016)
pt. 1. Theorizing harmful cultural practices -- pt. 2. Policy, legal developments and political discourse -- pt. 3. From FGM to cosmetic genital surgery -- pt. 4. Globalisation and emerging harmful cultural practices.